RETRACTED: Programming and processing of big data using python language in medicine - Ergashev, Otabek; Mamadaliev, Nurillo; Khonturaev, Sardorbek; Sobirov, Muzaffar (E3S web of conferences, 2024)
See the retraction notice E3S Web of Conferences 538 , 00001 (2024), https://doi.org/10.1051/e3sconf/202453800001